Upgrading Digital Marketing Skills Mahasiswa Komunikasi Penyiaran Islam UIN Ar-Ranniry Dalam Upaya Kesiapan Menghadapi Dunia Kerja - Syahril Furqany (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2021)
This study aims to train students to understand digital marketing, to find students' talents in the entrepreneurial world. The rapid development of the digital era is very important to be used in a positive direction. One of them is having digital marketing skills. This study uses Participatory Actions Research (PAR). By involving students actively in carrying out program activities. The results showed that in the early stages students did not know what digital marketing was. then students are provided with materials and practices for distributing digital marketing on social media. The results of the evaluation of students have understood and can practice marketing through digital or known as digital marketing. During the process of spreading messages through social media, it was held by students for ten consecutive days. The changes that are felt are increasing visitors to the website, increasing followers on Instagram and Facebook accounts, and increasing sales. The perceived impact is really real so that this can be used as an effort that is carried out systematically and measurably by other businesses.